PERENCANAAN PENGEMBANGAN DESA WISATA CIBUNTU OLEH DINAS PEMUDA OLAHRAGA DAN PARIWISATA KABUPATEN KUNINGAN DALAM MENINGKATKAN KUNJUNGAN WISATA (STUDI KASUS BIDANG DESTINASI PARIWISATA) - Winaningsih .; Hery Nariyah; Rifai Yusuf (Jurnal Ilmiah Publika, 2018)
ABSTRACT This research entitled "Planning of Cibuntu Village Tourism Development by Dinas Pemuda Olahraga dan Pariwisata Kabupaten Kuningan in Increasing Tourist Visit (Case Study of Tourism Destination)" This research objectives to find out the Village Tourism Development Planning Cibuntu by Dinas Pemuda Olahraga dan Pariwisata Kabupaten Kuningan in increasing visit tourism, to know the supporting factors and obstacles factor in the development planning of cibuntu tourism village by the Dinas Pemuda Olahraga dan Pariwisata Kabupaten Kuningan in improving the Visit of Tourism, and to know what efforts have been done by Dinas Pemuda Olahraga dan Pariwisata Kabupaten Kuningan in overcoming the obstacles factors.The research method used is qualitative method through descriptive approach by taking the research location in Dinas Pemuda Olahraga dan Pariwisata Kabupaten Kuningan and Cibuntu Tourism Village as supporting location. While the key informant is the Sector Head of Tourism Destination Dinas Pemuda Olahraga dan Pariwisata Kabupaten Kuningan and supporting informant is Movement Group Cibuntu Tourism Village and tour manager Cibuntu Tourism Village. Data collection techniques used are literature studies, observation, interviews and documentation as well as techniques testing the validity of data using triangulation techniques.The results of the Cibuntu Village Tourism Dinas Pemuda Olahraga dan Pariwisata Kabupaten Kuningan in increasing the Tourism Visit (Case Study of Tourism Destination) are viewed from dimensions according to Stoner James, AF (in Yayat Herujito 2006: 89) that is 1. Setting objectives (preserving the source the existing natural resources, increasing the number of tourist visits, improving the welfare of the community, empowering the community, creating creative industries in the community and increasing the original income of the district of Kuningan Regency 2. Determining the present situation (arrangement, clean up, develop rapidly), 3. Define the supporting and obstacles (supporting factors, natural beauty, adequate human resources, unique art and culture, and high community spirit while obstacles factors; Inadequate road infrastructure and Budget); 4. Develop a set of actions (cibuntu tourism village development based on Detail Engineering Design)